Integrated Metabolomics and Network Pharmacology Revealed Hong-Hua-Xiao-Yao Tablet’s Effect of Mediating Hormone Synthesis in the Treatment of Mammary Gland Hyperplasia - Gao, Ziqing; Mi, Rui; Cheng, Zhaoxi; Li, Xiaofeng; Zeng, Huawu; Wu, Gaosong; Zhao, Jing; Zhang, Weidong; Ye, Ji (Frontiers in Pharmacology, 2022)
Hong-Hua-Xiao-Yao Tablet (HHXYT) is a traditional Chinese medicine (TCM) formula approved for treating mammary gland hyperplasia (MGH), but the way it works has not yet been elucidated. In this study, the integrated metabolomics and network pharmacology strategy were applied to systemically reveal the mechanism of HHXYT in the treatment of MGH. Our pharmacodynamic study indicated that the proliferation of mammary gland was inhibited in rats, and serum levels disorder of estradiol and progesterone were reversed after HHXYT treatment. 54 compounds were identified from rat plasma after administration of HHXYT. 58 endogenous differential metabolites were detected in the serum metabolome, in which 31% were steroid lipids metabolites, while the steroid hormone biosynthesis was the most significant metabolic module. 7 targets, 6 herbs, and 17 ingredients were found to play key roles in HHXYT’s treatment of MGH. Among the 7 key targets, 3 targets (CYP11A1, HSD3B2, and CYP17A1) were directly involved in androgen synthesis, and 2 targets (AR and ESR1) were receptors for the direct action of androgens and estrogens. The bindings between the 5 targets with corresponding compounds were validated by molecular docking. The in vitro assay indicated that HHXYT (50 ng/ml) and its ingredient formononetin (3.2, 6.3, and 12.5 µM) could distinctly inhibit the increase of testosterone level induced by dexamethasone (10 µM) in thecal cells. In summary, this study illustrated that the mechanism of HHXYT’s treatment of MGH was to regulate hormone disorder. HHXYT could reduce estrogen-stimulated hyperplasia by inhibiting the production of its precursor androgen.